Coherency strains of H-phase precipitates and their influence on functional properties of nickel-titanium-hafnium shape memory alloys. (1st April 2018) - Amin-Ahmadi, Behnam; Pauza, Joseph G.; Shamimi, Ali; Duerig, Tom W.; Noebe, Ronald D.; Stebner, Aaron P.
Abstract: A Ni50.3 Ti41.7 Hf8 alloy was studied after two-step aging treatments consisting of 300 °C for 12 h followed by 550 °C for different times. An anomalous change in transformation temperatures was observed as the second aging time was increased from 7.5 to 13.5 h. Initially with increased aging time (0.5–7.5 h) at 550 °C, coherency strain fields about H-phase precipitates increased. The corresponding backstress favored martensite formation, hence an increase in transformation temperatures. However, a point was eventually reached where misfit dislocations relaxed those strain fields and the effect was reduced, resulting in a decrease in transformation temperatures. Graphical abstract: Image 1